Characterization of a Novel Moderately Thermophilic Solvent-Tolerant Esterase Isolated From a Compost Metagenome Library - Park, Ji-Min; Kang, Chul-Hyung; Won, Sung-Min; Oh, Ki-Hoon; Yoon, Jung-Hoon (Frontiers in Microbiology, 2020)
A novel esterase, EstCS1, was isolated from a compost metagenomic library. The EstCS1 protein, which consists of 309 amino acid residues with an anticipated molecular mass of 34kDa, indicated the highest amino acid identities to a predicted esterase (59%) from a cultured bacterium (AZV42415.1) and a predicted lipase/esterase (46%) from an uncultured bacterium (AAS77247.1). The phylogenetic analysis suggested that the EstCS1 belongs to the HSL family of lipolytic enzyme classification and contains a catalytic triad including Ser155-Asp255-His285. The Ser155 residue of the catalytic triad in the EstCS1 was located in the consensus active-site motif, GXSXG. Besides, a conserved HGGG motif placed in an oxyanion hole of the HSL family was discovered too. The EstCS1 demonstrated the highest activity toward p-nitrophenyl propionate (C3) and caproate (C6) and was normally stable up to 60°C with optimal activity at 50°C. In addition, an optimal activity was observed at pH 8, and the EstCS1 possessed its stability within the pH range between 5 to 10. Interestingly, EstCS1 had an outstanding stability in up to 30% (v/v) organic solvents and activity over 50% in the presence of 50% (v/v) acetone, ethanol, DMSO and DMF. The EstCS1 hydrolyzed sterically hindered tertiary alcohol esters of t-butyl acetate and linalyl acetate. Considering the properties of EstCS1 such as the moderate thermostability, stability against organic solvents and activity towards esters of tertiary alcohols, the EstCS1 must be worthwhile to be used for organic synthesis and related industrial applications.